Peningkatan PHBS melalui Pendekatan Pembelajaran Interaktif pada Siswa Sekolah Dasar - Kartika Setyaningsih Sunardi; Ratih Purwanti; Haryo Nugroho (Permata Indonesia, 2026)
Clean and Healthy Living Behavior (PHBS) is an important strategy in improving health status from an early age, especially inelementary school children. This community service activity aims to improve students' knowledge and skills related to PHBS throughan interactive educational approach. The activity was held on January 10, 2026 at SDN Deresan and SDN Caturtunggal 1 with atotal of 94 students. The material presented included waste sorting, washing hands with soap, brushing your teeth correctly, andchoosing healthy snacks. The methods used are interactive lectures, quizzes, simulations, and hands-on practice. The resultsshowed an increase in student understanding which was characterized by the ability to answer questions, active involvement inactivities, and the ability to practice healthy behaviors. Giving rewards has been proven to increase student motivation inparticipating in activities. Interactive-based PHBS education is effective in increasing awareness and healthy behavior in elementaryschool students.